Lack and Excess in the Filmic Representations of Justice - Tolentino, Rolando (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The essay examines the filmic representations of justice and the judiciary in Philippine cinema. The first section analyzes the conventions of the legal film" that uses the judiciary space as the locus of contestation of the filmic conflict. The second section formulates the filmic imagination of an inept judicial system in the country. The last section discusses the cultural politics involved in the film’s pessimistic representations of justice, in relation to the larger historical and social formations of the judicial institution. Using films such as Aida Macaraeg, Minsay Isang Gamu-gamo, Sa Kuko ng Aguila, and Bulaklak ng City Jail, the essay materializes the connections between the filmic representations, and the social and historical construction of the Philippine judiciary.